THE EFFECT OF INVESTMENT OPPORTUNITY SET AND BOOK TAX DIFFERENCES ON EARNINGS GROWTH WITH MANAGERIAL OWNERSHIP AS MODERATING (A STUDY ON BASIC MATERIAL AND INDUSTRIAL COMPANIES) - Lativa; Susi Dwimulyani (Asosiasi Dosen Muda Indonesia, 2026)
This study looks at how Book Tax Differences (BTD) and Investment Opportunity Set (IOS) affect earnings growth in industrial and raw material companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. To evaluate the impact of managerial ownership on earnings growth through IOS and BTD, managerial ownership is included as a moderator. This study uses quantitative methodology and uses secondary data from the company's website, idnfinancials.com, and the IDX website. A total of 95 observations were obtained from a sample of 19 companies with purposive sampling technique for sampling. Eviews 12 is the program used for data analysis. The findings of this study are that earnings growth is significantly influenced by IOS and BTD. Meanwhile, managerial ownership has a role in moderating the positive effect of BTD on Earnings Growth but does not moderate the effect of IOS on Earnings Growth of raw material and industrial companies. This study has novelty from the aspect of sample characteristics that are more focused on raw material and industrial companies by combining the theories of IOS, BTD, Earning of Growth (PL), Manajerial Ownership (KM), Firm Size (FS), DER, CR and including 3 control variables FS, DER, CR and moderating variables, namely managerial ownership which have not been raised in previous studies, especially for research on raw material and industrial companies.